Academic and Technical Obstacles to Distance Education in Light of the Covid-19 Pandemic from the Point of View of Students of the Department of Communication and Media at King Faisal University - Alhag Mohamed, Hisham Abdalla (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to identify the most significant academic and technical faced by remote education from the perspective of students in the Department of Communication and Media at King Faisal University, in light of the COVID-19 pandemic. Methodology: The study adopted a descriptive approach using the survey method and utilized a questionnaire tool to gather information from a study sample of 251 individuals selected through simple random probability sampling. Among the key questions posed to the study sample were inquiries about the main academic and technical obstacles encountered in the educational process during the COVID-19 pandemic. Results: The study yielded several results, including that 40.2% of the sample individuals agreed that the electronic platform at the university operates as required, while 30.7% of the sample individuals agreed that remote learning lectures are sometimes scheduled at inconvenient times for students. Conclusion: The study concluded by proposing solutions to address all technical difficulties faced by students during lectures and exams, suggesting the establishment of clear and consistent standards for assessments and grades used in remote education, and explaining them to students by the academic program designers at the college.